Pitfalls in Morphologic Diagnosis of Pathogens: Lessons Learned From the Pseudo-Cystoisospora Epidemic. (April 2021) - Gopinath, Arun; Alkhasawneh, Ahmad; Mubeen, Aysha; Makary, Raafat; Mohammed, Ibraheem; Baskovich, Brett
Multiple groups have recently reported involvement of the gallbladder mucosa of immunocompetent patients by cystoisospora organisms. However, this has recently been disproved with the support of molecular and ultrastructural studies. Here we present a summary of these events, recounting how this pseudo-Cystoisospora epidemic began and ended. This review also highlights the important role played by ancillary techniques in supplementing the morphologic diagnosis of pathogens.